MODIFIED SINGLE-ZONE MODEL OF RADIATION RECUPERATOR WITH MICROFINNED SURFACE (Metallurgy and Foundry Engineering, 2007)
Modified single-zone model of radiation recuperator with microfinned surface were elaborated. In this model the researches of heat transfer and hydraulic resistance microfinned elements were applied. To calculate the recuperator wall temperature weight mean temperature was used. By elaborated model radiation recuperator with microfinned surface to glass furnace were calculated. Single-zone model makes possible the project of small overall dimensions recuperators to industrial furnaces.